Single Regulator dalam Multi Bar Organisasi Advokat Untuk Masa Depan Advokat yang Independent - Diar, Adithiya; Alifri, Aqshal Habibillah; Bintang, Muhammad (Universitas Batanghari Jambi, 2024)
Several multi-interpretive provisions in the Advocate Law are considered to violate the constitutional rights of advocates to carry out their profession. Over the years, this has resulted in quarrels and disputes between advocates regarding organizational matters, this of course has an impact on advocates, new advocates and also people seeking justice. The research method used in this research is the normative juridical method. This research is included in descriptive analysis research, aiming to describe carefully the single bar organization, history, debates, rules of advocates. The single bar system must be interpreted as an organization that accommodates all advocates, starting from education, oaths, codes of ethics and enforcement of codes of ethics. advocates so that there are clear standards to guarantee that lawyers are qualified and recognized by the state to be able to proceed in court. Judging from the institutional perspective of advocate organizations at the present time, it can be said that they are still not organized. The main factor is the lack of clear standardization in carrying out their authority as an advocate. With government intervention in efforts to form a single forum for advocate organizations as mandated by the Advocate Law, this will be realized. The government or state can do this because it has the power to form legal products, namely laws, including the Law on Advocates. The ideal concept in this research shows that the institution of a multi-bar advocate organization with a single regulator can restore the dignity of advocacy as a noble profession or nobile officiating.